Intrinsic Transesterification Rate of Vegetable Oils - Han , Fon Yee (IRC, 2016)
Biodiesel, also known as fatty acid methyl esters, is a favorable alternative source of energy due to its numerous ecological advantages. The majority of biodiesel produced today are done with the transesterification of triglycerides from vegetable oils with a short-chained alcohol, mainly methanol, in the presence of a base catalyst. For the time being, most of the transesterification studies are using pseudo first order kinetics which does not reflect the precise phenomenon of the reaction. It is very likely that the reaction rate observed is affected by physical mass transfer effect due to low miscibility of the two reactant phases (methanol and oil) that forms two layers of liquid phase and subsequently slower the initial reaction rate. Therefore, this study will narrow down reaction zone to the interface between oil and methanol droplet by adding cosolvent to conduct the reaction in a single phase.